Visualizing the hidden environmental costs of fashion: A systemic functional-multimodal discourse analysis - Alan Jaelani; Ifan Iskandar; Ratna Dewanti (Siliwangi University, 2025)
In response to increasing environmental concerns regarding fashion waste, this study examines how digital campaign visuals construct and communicate environmental meanings through multimodal design. The data consist of four campaign visuals purposively selected from a single social media post published by the United Nations Environment Programme for the International Day of Zero Waste 2025. The visuals were selected based on their thematic relevance to fashion waste, multimodal richness, and representation of diverse visual strategies, including symbolic imagery, statistical emphasis, actional processes, and textual appeals. Drawing on the three metafunctions of Systemic Functional Linguistics and Kress and van Leeuwen’s framework of visual social semiotics, this study analyzes how representational, interactive, and compositional meanings are realized in the campaign visuals. Using qualitative content analysis, the findings show that the visuals combine conceptual symbolism and actional representation to reveal the hidden environmental costs of fashion, such as pollution, water overuse, and carbon emissions. Most images adopt an observer-oriented perspective that positions viewers as reflective witnesses rather than direct participants, while selective use of close-up imagery and vivid colour strengthens emotional engagement and ethical awareness. Compositional strategies, including information value, salience, and contrast, are used to prioritize key environmental messages and guide interpretation. The study reveals how strategic visual design enhances the persuasive power of environmental campaigns and offers practical implications for environmental communicators and campaign designers seeking to address fashion waste through effective visual communication.Keywords: Fashion waste, Metafunctions, Multimodal Discourse Analysis, Visual social semiotics, Representational, Interactive, compositional